Postcoloniality, interculturality and cultural identity: the African foreign culture classroom as a postcolony (2006)
The experience of colonialism and the neo-colonial practices of the Western Metropole, including the categorization of Africa as area in the disciplinary structuring of knowledge in the academia, sustain in the African teacher of Western culture, in the least, an ambivalent attitude towards the African cultural self and sets off, as well, an undercurrent of cultural asymmetry and cultural identity conflict in the African foreign culture classroom. This ambivalent attitude potentially affects the representation of both the African and the Western cultural identities and shapes the attitude of the African learner of Western culture towards his/her African cultural identity. This paper emphasizes the critical positioning of the (African) teacher of Western cultures to African learners in the cultural identity dialogue between Africa and the West and posits that appropriate and authentic knowledge both of the West and Africa, cultural self-knowledge and cultural self-acceptance are critical base knowledge required of the teacher - of Western culture to African .learners. This base knowledge combined with a “postcolonial Intercultural” model to foreign culture teaching and learning will enable the teacher to deal with the postcoloniality, asymmetry and conflict of cultural identities inherent in the African foreign culture classroom.